Research on the motivation of pharmaceutical workers in pharmacies - T. P. Zarichna; T. S. Brytanova; T. S. Raikova; Ye. H. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of work was to study the motivating and demotivating factors of the activity of pharmaceutical staff and the conditions of increasing their work activity.